2015
DOI: 10.1111/medu.12633
|View full text |Cite
|
Sign up to set email alerts
|

The effect of continuing professional development on public complaints: a case-control study

Abstract: The findings demonstrate a positive relationship between participation in the national CPD programmes of the CFPC and RCPSC, and lower numbers of public complaints received by the CPSO. As certification bodies and regulators alike are increasingly mandating CPD, they are encouraged to continually evaluate the effectiveness of their programmes to maximise programme impact on physician performance at the population level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
(41 reference statements)
0
23
0
Order By: Relevance
“…These studies have demonstrated a clear and positive relationship between CPD participation and diverse measures of physician performance, including peer assessment scores in a practice setting, 4 lower number of public complaints to relevant regulatory bodies 5 and quality of professional practice. 6 Against the backdrop of a challenging economic environment, Ireland's health system has experienced significant budgetary pressure and this has produced a decrease in front-line staff morale and an increase in international migration.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated a clear and positive relationship between CPD participation and diverse measures of physician performance, including peer assessment scores in a practice setting, 4 lower number of public complaints to relevant regulatory bodies 5 and quality of professional practice. 6 Against the backdrop of a challenging economic environment, Ireland's health system has experienced significant budgetary pressure and this has produced a decrease in front-line staff morale and an increase in international migration.…”
Section: Introductionmentioning
confidence: 99%
“…On the opposite side of the coin, the physicians in Wenghofer et al . 's sample who did not participate in CPD were more likely to have a complaint lodged about them. This poses questions which remain unanswered about whether participating in CPD is protective or whether physicians who lack the desire, insight and motivation to adhere to their peers’ expectations and regulatory requirements are more likely to have lower professional standards.…”
mentioning
confidence: 99%
“…In this issue of Medical Education , Wenghofer and colleagues report an analysis of the effect of CPD on public complaints using a case–control study. The effects of CPD were examined as a whole and in the three sub‐categories of: (i) peer‐reviewed and accredited activities; (ii) unaccredited activities, and (iii) individual needs‐based activities, which included reflective activities or exercises.…”
mentioning
confidence: 99%
See 2 more Smart Citations